The Role of Internet Utilization Among SMEs on Household Welfare in Indonesia - Ariska N. Rini; Lienggar Rahadiantino (Jurnal Ekonomi Indonesia, 2020)
The Internet has a significant influence on poverty alleviation and economic growth. Internet involvement in small-medium enterprises (SMEs) has the opportunity to create a better level of welfare. Using data from the fifth wave of the Indonesian Family Life Survey (IFLS), this study aims to analyze the impact of internet utilization on household welfare among two groups, household enterprises with internet use for business and without internet use for business. The results of the Propensity Score Matching (PSM) method mention that household enterprises with internet for business purposes have higher household per capita expenditure, food consumption, and non-food expenditure than household enterprises without internet use. Another interesting result finds that household enterprises are likely to use the internet only if household heads at a young age and business establish less than one year.